The impact of structured support groups for pregnant South African women recently diagnosed HIV positive. - Mundell, Jonathan P; Visser, Maretha J; Makin, Jennifer D; Kershaw, Trace S; Forsyth, Brian W C; Jeffery, Bridget; Sikkema, Kathleen J (Women & health, 2011)
The authors of this study evaluated a structured 10-session psychosocial support group intervention for newly HIV-diagnosed pregnant South African women. Participants were expected to display increases in HIV disclosure, self-esteem, active coping and positive social support, and decreases in depression, avoidant coping, and negative social support. Three hundred sixty-one pregnant HIV-infected women were recruited from four antenatal clinics in Tshwane townships from April 2005 to September 2006. Using a quasi-experimental design, assessments were conducted at baseline and two and eight months post-intervention. A series of random effects regression analyses were conducted, with the three assessment points treated as a random effect of time. At both follow-ups, the rate of disclosure in the intervention group was significantly higher than that of the comparison group (p<0.001). Compared to the comparison group at the first follow-up, the intervention group displayed higher levels of active coping (t=2.68, p<0.05) and lower levels of avoidant coping (t=-2.02, p<0.05), and those who attended at least half of the intervention sessions exhibited improved self-esteem (t=2.11, p<0.05). Group interventions tailored for newly HIV positive pregnant women, implemented in resource-limited settings, may accelerate the process of adjusting to one's HIV status, but may not have sustainable benefits over time.
Keywords: Adaptation, Psychological; Adult; Avoidance Learning; Case-Control Studies; Female; Follow-Up Studies; Health Resources; HIV Seropositivity; Humans; Poverty; Pregnancy; Pregnancy Complications, Infectious; Regression Analysis; Self Concept; Self Disclosure; Self-Help Groups; Social Support; South Africa; Young Adult